The Role of Social Media in Political Activism and Social Movements: Mobilizing Support, Amplifying Voices, and Shaping Political Discourse - Meisuri Meisuri (Penelitian dan Pengembangan Ilmu, 2024)
Social media has become a major force in political activism and social movements, significantly influencing mobilization, amplification of voices, and political discourse. This research aims to explore how social media influences the formation of public opinion and political discourse regarding controversial issues by using the PRISMA method for collecting articles. The research results show that social media expands the reach of political discourse and increases public engagement, but also raises challenges such as polarization and the spread of disinformation. The implications of this research include the need for better regulation and more careful platform design to reduce negative impacts and promote constructive communication in politics.